Integration of children's songs in Indonesian language learning at Muslim Santitham Foundation School, Thailand: An experience in teaching BIPA - Kusmiatun, Ari; Adam, Nadda (COPE: Caraka Olah Pikir Edukatif, 2025)
Learning Indonesian for foreign speakers (BIPA) at the elementary school level requires a fun, communicative, and suitable approach for the child’s age and development. An effective medium in supporting this learning is children's songs. Songs can help children develop their ability to listen, pronounce, and understand language naturally. This study aims to describe the effectiveness, benefits, and challenges of integrating children's songs into BIPA learning at the Muslim Santitham Foundation School in Thailand. This research employed qualitative descriptive methods. Data collection techniques were conducted through observation, interviews, and documentation of student learning outcomes. The research subjects were 32 elementary school students (A1). The data analysis technique used the Miles and Huberman model, consisting of three main steps, namely data reduction, data presentation, and drawing conclusions/verification. The results of the study show that the use of children's songs can increase students’ active participation, strengthen basic vocabulary mastery, and create a pleasant learning atmosphere. However, several challenges, such as limited audio-visual media and differences in students’ language ability levels, need special attention. Children’s songs have proven to be a potential medium in BIPA learning for children, especially in rebuilding the closeness of the Malay language and culture in the southern region of Thailand